Hubungan Kebiasaan Konsumsi Kopi Terhadap Kejadian Dispepsia di Puskesmas Pamengkang Kabupaten Cirebon Tahun 2023 - Yusuf, Ade; Nurmawan, Yanuar Ari; Suhaeni, Eni (Jurnal Ners, 2024)
Dyspepsia is an upper gastrointestinal disorder that characterized by combination of disturbing manifestations or upper abdominal discomfort. Coffee is one of the factors can cause dyspepsia. To analyze the relationship between coffee consumption habits and the incidence of dyspepsia and to determine the effect of the respondent's characteristics (gender, age) and coffee consumption habits on the incidence of dyspepsia at the Pamengkang Health Center, Cirebon Regency in 2023. Observational analytic study used a cross-sectional design with Spearman's test to analyze the relationship between coffee consumption habits and dyspepsia and used a logistic regression test to determine the effect of respondent characteristics and coffee consumption habits on dyspepsia events at Pamengkang Health Center, Cirebon Regency in 2023. Spearman correlation test analysis obtained a p value of 0.123 (p > 0.05) which means that there is no relationship between coffee consumption habits and the incidence of dyspepsia and the logistic regression test in this study showed an effect value of 9.3% in this study. There is no significant relationship between the relationship between coffee consumption habits and the incidence of dyspepsia at the Pamengkang Public Health Center, Cirebon Regency in 2023. And the effect value of the characteristics of the respondents and coffee consumption habits on the incidence of dyspepsia is 9.3%.